A STUDY OF READING DIFFICULTIES IN ENGLISH LANGUAGE LEARNING (World Bulletin of Social Sciences, 2026)
This study examines the main difficulties students face in reading comprehension in English as a foreign language. Reading is an essential skill for academic success, yet many learners struggle to understand texts effectively. The purpose of this research is to identify common reading problems and explore strategies that can improve comprehension. A survey was conducted among EFL students using a questionnaire with both closed and open-ended questions. The results show that the most significant challenges include unfamiliar vocabulary, complex sentence structures, and difficulty identifying main ideas. In addition, issues such as lack of concentration and slow reading speed were reported. The findings are consistent with previous research, which highlights vocabulary and reading strategies as key factors. The study concludes that using techniques such as skimming, scanning, and regular reading practice can help improve students’ reading comprehension skills.